(untitled) (Fiep Bulletin - online, 2017)
Introduction: Stroke (stroke), or stroke, also known as stroke, is characterized by the rapid loss of neurologicalfunction, due to clogging by disruption of blood supply to brain structures or disruption causing The blood that supports the brainwith oxygen and glucose, transported by the cerebral blood vessels, stop reaching the region, causing the loss of the functionalityof the neurons. Objective: The present study intends to demonstrate a methodology to follow the post-stroke recovery work andto verify the possible changes in general quality of life parameters, through the vital signs of these individuals, after a regularphysical activity program and Recreational Method: Dialogues were carried out in order to raise awareness and establishpreventive strategies. For the anthropometric analysis were collected weight, height and hip and waist circumferences. Bodymass index (BMI) and waist hip ratio (WHR) were used to assess nutritional status. In addition, the heart rate per minute in restand exertion was measured with the use of a Polar frequency gauge. A digital blood pressure meter was used to collect systolicand diastolic blood pressure. Results: The patient studied during the two years had BMI and WHR above the ideal, but nosignificant variation was identified over the years. Only the resting heart rate of January 2015 was above ideal. During the othermonths of 2015 and 2016, vital parameters were within normal range. Conclusion: After the work performed, the patientresearched reported improvement in physical, emotional, motivational, social conditions and increased independence in dailyactivities.